Predictive Model to Evaluate Accommodation of Conflict Management Strategies and Board Performance of Oil and Gas Companies in Port Harcourt - SN, Eluozo; Johnson, Ukpong Uwem (Journal of Advanced Research in Petroleum Technology & Management; Vol 6 No 1&2 (2020): Journal of Advanced Research in Petroleum Technology and Management, 2021)
This paper evaluates accommodation of conflict management strategies and board performances in the oil and gas sector. The study detail the reflection of effectiveness, efficiency and productivity as the answer to thorough effectiveness in accommodation of conflict management in oil and gas sector, these parameters in the system express their efficacy on conflict management in these multinationals, these imply that for thorough efficiency, this variable must work simultaneously for an effective and efficient structural organization that can be a leading multinational sector in oil and gas environment. The study observed Linearized result from graphical representation explaining predominant lower efficiency and little higher efficiency in accommodation of conflict management in oil and gas companies. These experience from the study monitor the system from generated simulation values that describe the growth exponential phase of accommodation conflict strategic management, despite exponential phase, it experiences lower parameters showing it poor efficiency observed in the study, few periods observed higher effective accommodated conflict strategic management, the developed model stimulation values were subjected to validation and both parameters generated favourable fits, the study expressed the deficiency on accommodation of conflict management strategy thus developed models that can monitor the fluctuation and progressive state of accommodation conflict management strategy, it defined the reflection of other parameters that express the behaviour of the system in terms of a conceptual approach to monitoring these type of strategic management in oil and gas companies. How to cite this article:  Eluozo SN, Johnson UU. Predictive Model to Evaluate Accommodation of Conflict Management Strategies and Board Performance of Oil and Gas Companies in Port Harcourt. J Adv Res Petrol Tech Mgmt 2020; 6(1&2): 22-29.